The land use suitability concept: Introduction and an application of the concept to inform sustainable productivity within environmental constraints. (August 2018) - McDowell, R.W.; Snelder, T.; Harris, S.; Lilburne, L.; Larned, S.T.; Scarsbrook, M.; Curtis, A.; Holgate, B.; Phillips, J.; Taylor, K.
Highlights: Some land practices impair surface water quality and may also not be the best productive use of land. The land use suitability (LUS) concept is designed to inform better land use decisions. The first application of LUS focuses on balancing productive land and water quality. It has three indicators; production potential, relative contribution and pressure. The indicators can be used by many stakeholders to inform their ability to meet a water quality objective. Abstract: The Land Use Suitability (LUS) concept informs decision-making by providing stakeholders with integrated information about the economic, environmental, social and cultural consequences of land use choices. This paper addresses an application of the LUS concept: evaluating the suitability of land for sustained productivity subject to environmental constraints, as defined by water quality objectives. We refer to this application of the LUS concept as 'Productivity within Environmental Constraints' (PEC). A PEC assessment uses three indicators to evaluate land-water systems: 1) productive potential, describing the inherent productive and economic potential of land parcel s ; 2) relative contribution, describing the potential for a land parcel to contribute contaminants (relative to other land parcels) to downstream receiving environments; and 3) pressure, describing the contaminant load delivered to a receiving environment compared to the load that ensures that environmental objectives are met. The three indicators can be expressed categorically, mapped at catchment to national scales, and used to support strategic land assessments and plan land development and investment.